2002
DOI: 10.4049/jimmunol.169.3.1270
|View full text |Cite
|
Sign up to set email alerts
|

The CD154-CD40 T Cell Costimulation Pathway Is Required for Host Sensitization of CD8+ T Cells by Skin Grafts Via Direct Antigen Presentation

Abstract: Although the CD154-CD40 T cell costimulation pathway has been shown to mediate alloimmune responses in normal recipients, little is known about its role in sensitized hosts. In this work, by using novel models of cardiac allograft rejection in skin-sensitized CD154- and CD40-deficient mice, we reaffirm the key role of CD154-CD40 signaling in host sensitization to alloantigen in vivo. First, we identified CD8+ T cells as principal effectors in executing accelerated rejection in our model. Disruption of CD154-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
6
36
0
Order By: Relevance
“…This complements our previous studies (19,25) and further points toward the CD8 ϩ T cell as the principle target of the CD154 costimulation blockade in organ transplantation.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…This complements our previous studies (19,25) and further points toward the CD8 ϩ T cell as the principle target of the CD154 costimulation blockade in organ transplantation.…”
Section: Discussionsupporting
confidence: 70%
“…We have previously shown that alloreactive CD8 ϩ T cell activation is inhibited in CD154 KO mice (19). This finding provided us with an adoptive cell transfer model system to elucidate putative components in the CD154 costimulation pathway that may lead to activation of alloreactive CD8 ϩ T cells.…”
Section: Cd154 Costimulation Pathway Activates Alloreactive Cd8 ϩ T Cmentioning
confidence: 97%
See 2 more Smart Citations
“…By using MHC fully mismatched skin grafts as alloantigen stimulant, we showed that alloreactive CD8 activation may proceed through CD4-dependent and -independent pathways, and that both pathways require CD154 costimulation (7,8). Furthermore, alloantigen-primed CD8 T cells in skin-sensitized recipients become CD154 independent when reactivated by a second skin graft, indicating the functional disparity between naive and memory alloreactive CD8 T cells (9).…”
mentioning
confidence: 97%